Effect of Copper and Nickel Content on the Corrosion Mechanisms in Ferritic Matrix Gray Cast Irons Under Simulated Marine Environments - Monsalve-Gonzalez, A; Artigas-Abuin, A; Sanchez-Villa, C; Allende-Seco, R; Bruna-Rivera, H (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This article investigated the influence of copper (Cu) and nickel (Ni) on atmospheric corrosion in gray cast iron under simulated marine conditions. The goal was to compare the effect of Cu and Ni addition in castings with weathering steels. Selected alloys were cast, cut, prepared, and heat-treated for microstructure homogenization. Accelerated corrosion tests were conducted using a salt spray chamber. Corroded samples were analyzed for corrosion thickness and deposits using scanning electron microscopy, X-ray diffraction, and electrochemical techniques. The results indicate that alloying elements significantly affect corrosion processes. In the long-term, Cu had a greater impact on the corrosion mechanisms than Ni. Both Cu and Ni exhibited similar effects on the corrosion mechanisms in gray cast iron and weathering steels. In the initial and final stages, the behavior was comparable to that of weathering steels, but in the intermediate stage, it differed from the literature, suggesting the presence of an additional mechanism between these stages. © 2024 by the authors.